2016
DOI: 10.1001/jamaoto.2015.3634
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Complications in Pediatric Tonsillectomy and Adenoidectomy in Ambulatory vs Inpatient Settings

Abstract: Large numbers of pediatric patients undergo T&A in ambulatory settings despite higher rates of complications in younger patients and patients with more comorbidities. Fortunately, a high percentage of these patients has been appropriately triaged to the inpatient setting. Further research is needed to elucidate the subgroups that warrant postoperative hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 30 publications
2
58
0
1
Order By: Relevance
“…Our study does have some significant limitations. Despite being the only tertiary children's hospital in the state, compared to the recent retrospective statewide review by Amoils et al, our 3‐year number is still relatively small. Likewise, the overall complication rate following tonsillectomy was expectedly low.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our study does have some significant limitations. Despite being the only tertiary children's hospital in the state, compared to the recent retrospective statewide review by Amoils et al, our 3‐year number is still relatively small. Likewise, the overall complication rate following tonsillectomy was expectedly low.…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, in their analysis, 33% of patients younger than 3 years old were not admitted after surgery despite these current guidelines. They therefore concluded that continued evaluation of which patients require admission following surgery is needed, and recommended that clinicians remain open to new information as it becomes available . An analysis out of the University of California Los Angeles of over 700 children undergoing tonsillectomy demonstrated no difference in complication rates between those <3 years old and those >3 years old .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The rate of primary hemorrhage in pediatric tonsillectomy patients has been reported to be between 1.1% and 3.4%, whereas hemorrhage that required treatment in the operating room is reported to be between 0.5% and 2.1%, and emergency department (ED) visits for either pain or dehydration have been reported to be between 7.6% and 13.3%. [5][6][7][8] The costs of patient visits to the ED in these cases range from $1,104 to $1,737, and when averaged over all children undergoing adenotonsillectomy (including those who did visit the ED) adds, on average, $189 to each patient's care. 8 In light of this, there is a significant opportunity to optimize outcomes after tonsillectomy and reduce complications by maximizing safe pain control in a way that limits readmission or the need for clarifying phone calls to the physicians office after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Tonsillectomies are mainly performed for the treatment of adenotonsillar hypertrophy (resulting in sleep‐disordered breathing) and recurrent tonsillitis . However, despite its safe reputation, tonsillectomies are associated with significant risk of morbidity and delays to recovery . Post‐operative complications include bleeding, respiratory compromise, infection, dehydration, pain, nausea and vomiting .…”
mentioning
confidence: 99%
“…However, despite its safe reputation, tonsillectomies are associated with significant risk of morbidity and delays to recovery . Post‐operative complications include bleeding, respiratory compromise, infection, dehydration, pain, nausea and vomiting . These adverse events are associated with patient suffering and additional health resource utilisation associated with prolonged hospital admission and emergency presentations …”
mentioning
confidence: 99%